ИЗУЧЕНИЕ ОПОЛЗНЕВОЙ ДЕЯТЕЛЬНОСТИ НА БЕРЕГАХ КАМСКОГО ВОДОХРАНИЛИЩА С ПРИМЕНЕНИЕМ ГИС-ТЕХНОЛОГИЙ - Калинин В.Г.; Назаров Н.Н.; Пьянков С.В.; Симиренов С.А.; Тюняткин Д.Г. (My University, 2004)
The spatial differentiation and intensity of the landslide deformation were investigated by large-scale tachymetry on the model test site. The data obtained were processed by means of GIS-technologies. The application of the MAP-algebra and mathematics-cartographic simulation has allowed to distinguish segments of the landslide with different direction and velocity of movements and to calculate their volumes and areas.
Keywords: 551.435.627(470.53)